2019
DOI: 10.1042/bsr20191255
|View full text |Cite|
|
Sign up to set email alerts
|

miRNA-103 promotes chondrocyte apoptosis by down-regulation of Sphingosine kinase-1 and ameliorates PI3K/AKT pathway in osteoarthritis

Abstract: Objectives: The aim of the present study was to determine the effects of miRNA-103 on chondrocyte apoptosis and molecular mechanisms in osteoarthritis (OA) progression. Methods: The cell proliferation, apoptosis, and recovery ability were measured by cell counting kit-8 (CCK-8), flow cytometry, and wound healing assays. The interaction of miRNA-103 and Sphingosine kinase-1 (SPHK1) were determined by using luciferase reporter assay. The expression of mRNA and proteins were measured by qRT-PCR and Western blot. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…In the researches of Soyocak [16] and others, miR-146a and miR-155 increased significantly in the progressive stage of OA, suggesting that they may be involved in the disease progression of OA. The researches by Li et al [17] have indicated that miR-103 can increase the level of chondrocyte apoptosis and promote the disease process of OA by inhibiting SPHK1 activity and PI3K/AKT pathway activation. miR-137, the main character of our study, was previously reported to be involved in the disease process of osteoporotic fracture.…”
Section: Introductionmentioning
confidence: 99%
“…In the researches of Soyocak [16] and others, miR-146a and miR-155 increased significantly in the progressive stage of OA, suggesting that they may be involved in the disease progression of OA. The researches by Li et al [17] have indicated that miR-103 can increase the level of chondrocyte apoptosis and promote the disease process of OA by inhibiting SPHK1 activity and PI3K/AKT pathway activation. miR-137, the main character of our study, was previously reported to be involved in the disease process of osteoporotic fracture.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating studies confirm that miRNAs figure prominently in OA progression. For example, miR-103 expression is significantly increased in the cartilage tissue of OA patients and rat models, and miR-103 can promote OA progression by down-regulating the PI3K/AKT pathway and reducing SPHK1 activity ( Li et al, 2019 ). MiR-146a expression is markedly raised in the OA model induced by IL-1β in vitro , and miR-146a can promote the pathogenesis of OA by targeting Smad4 to increase VEGF expression and inhibit the TGF-β signaling pathway ( Li et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…In OA chondrocytes it has been observed a number of up-regulated miRNAs. In particular, miR-9 down-regulates monocyte chemoattractant protein-induced protein 1 expression, promoting IL-6 expression and chondrocyte apoptosis [ 201 ]; miR-103 induces cell apoptosis and suppresses cell proliferation down-regulating PI3K/AKT pathway by blocking sphingosine kinase 1 expression [ 202 ]; miR-34a promotes apoptosis by directly regulating the silent information regulator 1 (SIRT1)/p53 signaling pathway [ 203 ] or through the delta-like protein 1 via PI3K/AKT pathway [ 204 ]. SIRT1, in particular, is a deacetylase playing a crucial role in the prevention of apoptosis, enhancing acetylated p53 and Bax and down-regulating Bcl-2.…”
Section: Apoptosis and Cartilage Calcificationmentioning
confidence: 99%